Diagnóstico do uso da Irrigação em Pequenas Propriedades Rurais na Região Oeste do Paraná - Schonwald, Celso (2005)
The implantation of projects of Irrigation in agricultural properties has busy significant space in the productive process of Brazilian agriculture. Despite the advantages that the technique demand, becomes necessary to consider the economic return of the investment applied for the implantation of the irrigation project, as also to know the practical ones of production, the availability of workmanship hand and the specified of the agriculturist in each project. With intention to foment this lack, this work had as objective to evaluate the partnereconomic implantation of irrigation systems and its economic viability and benefits, in small properties, the region west of the state of the Paraná, presenting methods for the financial evaluation of these projects and demonstrating as to analyze an irrigation project and if this is viable or not. With the diagnosis we can conclude that the lack of experience of the producers was determinative in the results; the TIR was of 44%a.a.;25%a.a. e 11%a.a.; the TR was minor who 2; 3 and 3 years, for the cultures of the tomatoe, strawberry and watermelon, respectively; the culture of the broccolis and cucumber could not economically be evaluated.